Asphalt waterproof coiled material and preparation method thereof
By combining the boron nitride nanosheets wrapped in the asphalt waterproof roll with SBS, the modified asphalt is formed, which solves the performance problems of traditional asphalt waterproof rolls at different temperatures, and achieves better high-temperature stability, low-temperature crack resistance and waterproofing performance.
Patent Information
- Application Number
- CN202411992930.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Traditional asphalt waterproof coils are prone to soften and flow at high temperatures and easily brittle and cracked at low temperatures, resulting in poor use in different seasons, affecting their service life and waterproof performance.
Boron nitride nanosheets wrapped in porous silicone are used as modifiers to form modified bitumen by combining with SBS and asphalt matrix. The modified asphalt is prepared by ultrasonic and reflux, and is coated on the surface of the tire base for flattening and natural cooling.
The needle inlet, softening point and ductility of modified asphalt is significantly improved, its high-temperature stability, low-temperature crack resistance and normal temperature flexibility are improved, and the tensile performance, heat resistance and waterproofness of asphalt waterproof rolls are improved.
Smart Images

Figure BDA0005224016200000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of roll materials, and in particular to an asphalt waterproof roll material and a preparation method thereof. Background Art
[0002] Asphalt waterproofing membrane is an important material widely used in building waterproofing projects, and its performance directly affects the waterproofing effect and service life of the building. As a basic building material, asphalt waterproofing membrane needs to have excellent weather resistance, waterproofness and mechanical properties to adapt to complex construction environments and long-term use requirements. However, traditional asphalt waterproofing membranes usually use matrix asphalt as the main raw material. Although the matrix asphalt has certain waterproof properties, it is easy to soften and flow at high temperatures and easy to crack at low temperatures, causing it to deform or flow easily in high temperature seasons, and easy to crack in low temperature environments, seriously affecting its service life and waterproofing effect. Therefore, in order to improve the comprehensive performance of asphalt waterproofing membranes, in recent years, modifying asphalt by adding modifiers has become the main means to improve its performance.
[0003] SBS (styrene-butadiene-styrene block copolymer) modified asphalt is widely used because of its excellent high temperature stability, low temperature crack resistance and flexibility. SBS is a thermoplastic elastomer that can form an interpenetrating network structure in an asphalt matrix, thereby significantly improving the elasticity and toughness of asphalt, making it have a stronger anti-deformation ability at high temperatures, and maintaining good flexibility at low temperatures, meeting the needs of building waterproofing projects. However, SBS modified asphalt still has some problems in practical applications, such as the lack of compatibility between SBS and asphalt matrix, resulting in unstable modification effect. Due to the polarity difference between SBS and asphalt matrix, it is easy to phase separate in asphalt, and it is impossible to form a uniform distribution in the matrix, resulting in the modification effect being difficult to maintain for a long time. In addition, small molecular organic matter in the asphalt matrix is easy to migrate and volatilize, which will not only affect the mechanical properties and viscoelasticity of asphalt, but also accelerate the aging of asphalt, further affecting the long-term performance of modified asphalt. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an asphalt waterproofing membrane and a preparation method thereof, so as to improve the mechanical properties, heat resistance and waterproofness of the asphalt waterproofing membrane.
[0005] Based on the above purpose, the present invention provides an asphalt waterproofing coiled material, which is obtained by coating modified asphalt on the surface of a base, flattening it, and naturally cooling it.
[0006] Furthermore, the preparation method of the modified asphalt is as follows:
[0007] (1) adding boron nitride nanosheets to a mixed solution of anhydrous ethanol and deionized water, ultrasonicating for 20-40 minutes, then adding hexadecyltrimethylammonium bromide, stirring for 20-40 minutes, then adding 1,4-bis(triethoxysilyl)benzene, phenyltrimethoxysilane and vinyltrimethoxysilane, heating to 40-50° C., stirring for 10-15 hours, centrifuging, washing with water, washing with alcohol, and drying to obtain alkenyl organosilicon-coated boron nitride nanosheets;
[0008] (2) adding the alkenyl organosilicon-coated boron nitride nanosheets and the hydrochloric acid aqueous solution into anhydrous ethanol, ultrasonicating for 20-40 minutes, refluxing at 95-105° C. for 20-28 hours, centrifuging, washing with alcohol, and drying to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0009] (3) Add asphalt to cyclohexane oil, heat to 185-195°C, stir for 20-40 minutes, then add SBS, continue stirring for 1.5-2.5 hours, then add porous olefin-based organosilicon-coated boron nitride nanosheets and isopropylbenzene hydroperoxide, continue stirring for 0.5-1.5 hours, then add talcum powder, continue stirring for 1.5-2.5 hours, discharge, and obtain modified asphalt.
[0010] Preferably, in step (1), the average thickness of the boron nitride nanosheets is 200-400 nm, and the average sheet diameter is 3-5 μm.
[0011] Preferably, in step (1), the weight ratio of boron nitride nanosheets, anhydrous ethanol, deionized water, hexadecyltrimethylammonium bromide, 1,4-bis(triethoxysilyl)benzene, phenyltrimethoxysilane and vinyltrimethoxysilane is 10:700-1100:50-150:0.3-0.8:3-7:51-25:1-3.
[0012] 4. The asphalt waterproofing membrane according to claim 1, characterized in that in the step (2), the weight ratio of the boron nitride nanosheets wrapped by alkenyl organosilicon, the hydrochloric acid aqueous solution and the anhydrous ethanol is 10:8-12:150-250.
[0013] Preferably, the concentration of the aqueous hydrochloric acid solution in step (2) is 1.5-2.5 mol / L.
[0014] Preferably, the asphalt in step (3) is 70# asphalt.
[0015] Preferably, the SBS in step (3) is linear SBS.
[0016] Preferably, the cyclopentane oil in step (3) is one of cyclopentane oil 4006 and cyclopentane oil 4010.
[0017] Preferably, in step (3), the weight ratio of asphalt, cyclohexane oil, SBS, porous olefin-based organosilicon-coated boron nitride nanosheets, cumene hydroperoxide and talc is 100:20-30:7-9:3-7:0.06-0.1:6-10.
[0018] Furthermore, the present invention also provides a method for preparing an asphalt waterproofing membrane, comprising the following steps: coating the modified asphalt on the surface of a polyester base with a thickness of 3-5 mm, flattening, and naturally cooling to obtain the asphalt waterproofing membrane.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides an asphalt waterproofing membrane and a preparation method thereof. By using phenyltrimethoxysilane, 1,4-bis(triethoxysilyl)benzene and vinyltrimethoxysilane as the skeleton to construct a porous organosilicon wrapped with boron nitride nanosheets, the needle penetration, softening point and ductility of the modified asphalt are significantly improved, and the modified asphalt is endowed with good high temperature stability, low temperature crack resistance and room temperature flexibility. The unique structure of the porous organosilicon can synergistically adsorb small molecular organic matter in the asphalt matrix, reduce its migration and volatilization, and thus improve the stability and comprehensive performance of the asphalt. The introduction of benzene rings enhances the compatibility of boron nitride nanosheets with SBS and asphalt matrix, further improves the softening point and ductility of the modified asphalt, and at the same time improves the tensile properties, heat resistance and waterproofness of the waterproofing membrane.
[0021] The present invention provides an asphalt waterproofing coiled material and a preparation method thereof. 1,4-bis(triethoxysilyl)benzene is used to adjust the organosilicon pore structure and environment on the surface of boron nitride nanosheets, so that it can adsorb more small molecules in the asphalt matrix to form an elastic surface structure, which significantly improves the flexibility and durability of the modified asphalt. Vinyl trimethoxysilane introduces alkenyl groups on the surface of organosilicon to form a cross-linked network structure with SBS, further enhancing the mechanical properties and thermal stability of the asphalt. The waterproofing coiled material prepared thereby has excellent tensile properties, heat resistance and waterproof properties, and can meet the long-term use requirements in complex environments. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] The average thickness of the boron nitride nanosheets in the specific embodiment of the present invention is 320 nm, and the average sheet diameter is 4.2 μm; the asphalt is 70# asphalt; the SBS is linear SBS purchased from Huizhou Li Changrong Rubber Co., Ltd., brand 3537, and the cyclopentane oil is cyclopentane oil 4006.
[0024] Embodiment 1:
[0025] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 700 g of anhydrous ethanol and 50 g of deionized water, ultrasonicating for 20 min, adding 0.3 g of hexadecyltrimethylammonium bromide, stirring for 20 min, adding 3 g of 1,4-bis(triethoxysilyl)benzene, 15 g of phenyltrimethoxysilane and 1 g of vinyltrimethoxysilane, heating to 40 °C, stirring for 10 h, centrifuging, washing with water, washing with alcohol, and obtaining alkenyl organosilicon-coated boron nitride nanosheets;
[0026] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 8 g of a 1.5-2.5 mol / L hydrochloric acid aqueous solution to 150 g of anhydrous ethanol, ultrasonicating for 20 min, refluxing at 95° C. for 20 h, centrifuging, washing with alcohol, and drying at 55° C. for 20 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0027] (3) 100 g of asphalt was added to 20 g of cyclohexane oil, the temperature was raised to 185 °C, and the mixture was stirred for 20 min. Then, 7 g of SBS was added, and the mixture was stirred for 1.5 h. Then, 3 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.06 g of cumene hydroperoxide were added, and the mixture was stirred for 0.5 h. Then, 6 g of talc was added, and the mixture was stirred for 1.5 h. The mixture was discharged to obtain modified asphalt.
[0028] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0029] Embodiment 2:
[0030] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 900 g of anhydrous ethanol and 100 g of deionized water, ultrasonicating for 30 min, adding 0.5 g of hexadecyltrimethylammonium bromide, stirring for 30 min, adding 5 g of 1,4-bis(triethoxysilyl)benzene, 20 g of phenyltrimethoxysilane and 2 g of vinyltrimethoxysilane, heating to 45° C., stirring for 12 h, centrifuging, washing with water, and washing with alcohol to obtain alkenyl organosilicon-coated boron nitride nanosheets;
[0031] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 10 g of 2 mol / L hydrochloric acid aqueous solution to 200 g of anhydrous ethanol, ultrasonicating for 30 min, refluxing at 100° C. for 24 h, centrifuging, washing with alcohol, and drying at 60° C. for 24 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0032] (3) 100 g of asphalt was added to 25 g of cyclohexane oil, the temperature was raised to 190 °C, and the mixture was stirred for 30 min. Then 8 g of SBS was added, and the mixture was stirred for 2 h. Then 5 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.08 g of cumene hydroperoxide were added, and the mixture was stirred for 1 h. Then 8 g of talc was added, and the mixture was stirred for 2 h. The modified asphalt was obtained.
[0033] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0034] Embodiment 3:
[0035] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 1100 g of anhydrous ethanol and 150 g of deionized water, ultrasonicating for 40 min, adding 0.8 g of hexadecyltrimethylammonium bromide, stirring for 40 min, adding 7 g of 1,4-bis(triethoxysilyl)benzene, 25 g of phenyltrimethoxysilane and 3 g of vinyltrimethoxysilane, heating to 50° C., stirring for 15 h, centrifuging, washing with water, and washing with alcohol to obtain alkenyl organosilicon-coated boron nitride nanosheets;
[0036] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 12 g of a 2.5 mol / L hydrochloric acid aqueous solution to 250 g of anhydrous ethanol, ultrasonicating for 40 min, refluxing at 105° C. for 28 h, centrifuging, washing with alcohol, and drying at 65° C. for 28 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0037] (3) Add 100 g of asphalt to 30 g of cyclohexane oil, heat to 195 °C, stir for 40 min, add 9 g of SBS, continue stirring for 2.5 h, add 7 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.1 g of cumene hydroperoxide, continue stirring for 1.5 h, add 10 g of talc, continue stirring for 2.5 h, discharge, and obtain modified asphalt;
[0038] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0039] Comparative Example 1:
[0040] The difference between Comparative Example 1 and Example 2 is that the phenyltrimethoxysilane in step (1) is replaced by tetramethoxysilane;
[0041] The specific steps are as follows:
[0042] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 900 g of anhydrous ethanol and 100 g of deionized water, ultrasonicating for 30 min, adding 0.5 g of hexadecyltrimethylammonium bromide, stirring for 30 min, adding 5 g of 1,4-bis(triethoxysilyl)benzene, 20 g of tetramethoxysilane and 2 g of vinyltrimethoxysilane, heating to 45° C., stirring for 12 h, centrifuging, washing with water, and washing with alcohol to obtain alkenyl organosilicon-coated boron nitride nanosheets;
[0043] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 10 g of 2 mol / L hydrochloric acid aqueous solution to 200 g of anhydrous ethanol, ultrasonicating for 30 min, refluxing at 100° C. for 24 h, centrifuging, washing with alcohol, and drying at 60° C. for 24 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0044] (3) 100 g of asphalt was added to 25 g of cyclohexane oil, the temperature was raised to 190 °C, and the mixture was stirred for 30 min. Then 8 g of SBS was added, and the mixture was stirred for 2 h. Then 5 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.08 g of cumene hydroperoxide were added, and the mixture was stirred for 1 h. Then 8 g of talc was added, and the mixture was stirred for 2 h. The modified asphalt was obtained.
[0045] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0046] Comparative Example 2:
[0047] The difference between Comparative Example 2 and Example 2 is that 1,4-bis(triethoxysilyl)benzene in step (1) is replaced by phenyltrimethoxysilane;
[0048] The specific steps are as follows:
[0049] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 900 g of anhydrous ethanol and 100 g of deionized water, ultrasonicating for 30 min, adding 0.5 g of hexadecyltrimethylammonium bromide, stirring for 30 min, adding 25 g of phenyltrimethoxysilane and 2 g of vinyltrimethoxysilane, heating to 45 ° C, stirring for 12 h, centrifuging, washing with water, washing with alcohol, and obtaining alkenyl organosilicon-coated boron nitride nanosheets;
[0050] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 10 g of 2 mol / L hydrochloric acid aqueous solution to 200 g of anhydrous ethanol, ultrasonicating for 30 min, refluxing at 100° C. for 24 h, centrifuging, washing with alcohol, and drying at 60° C. for 24 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0051] (3) 100 g of asphalt was added to 25 g of cyclohexane oil, the temperature was raised to 190 °C, and the mixture was stirred for 30 min. Then 8 g of SBS was added, and the mixture was stirred for 2 h. Then 5 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.08 g of cumene hydroperoxide were added, and the mixture was stirred for 1 h. Then 8 g of talc was added, and the mixture was stirred for 2 h. The modified asphalt was obtained.
[0052] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0053] Comparative Example 3:
[0054] The difference between Comparative Example 3 and Example 2 is that the vinyl trimethoxysilane in step (1) is replaced by phenyl trimethoxysilane;
[0055] The specific steps are as follows:
[0056] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 900 g of anhydrous ethanol and 100 g of deionized water, ultrasonicating for 30 min, adding 0.5 g of hexadecyltrimethylammonium bromide, stirring for 30 min, adding 5 g of 1,4-bis(triethoxysilyl)benzene and 22 g of phenyltrimethoxysilane, heating to 45 ° C, stirring for 12 h, centrifuging, washing with water, washing with alcohol, and obtaining alkenyl organosilicon-coated boron nitride nanosheets;
[0057] (2) adding 10 g of alkenyl organosilicon-coated boron nitride nanosheets and 10 g of 2 mol / L hydrochloric acid aqueous solution to 200 g of anhydrous ethanol, ultrasonicating for 30 min, refluxing at 100° C. for 24 h, centrifuging, washing with alcohol, and drying at 60° C. for 24 h to obtain porous alkenyl organosilicon-coated boron nitride nanosheets;
[0058] (3) 100 g of asphalt was added to 25 g of cyclohexane oil, the temperature was raised to 190 °C, and the mixture was stirred for 30 min. Then 8 g of SBS was added, and the mixture was stirred for 2 h. Then 5 g of porous olefin-based organosilicon-coated boron nitride nanosheets and 0.08 g of cumene hydroperoxide were added, and the mixture was stirred for 1 h. Then 8 g of talc was added, and the mixture was stirred for 2 h. The modified asphalt was obtained.
[0059] (4) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0060] Comparative Example 4:
[0061] The difference between Comparative Example 4 and Example 2 is that the porous alkenyl organosilicon-wrapped boron nitride nanosheets in step (3) are replaced with alkenyl organosilicon-wrapped boron nitride nanosheets;
[0062] The specific steps are as follows:
[0063] (1) adding 10 g of boron nitride nanosheets to a mixed solution of 900 g of anhydrous ethanol and 100 g of deionized water, ultrasonicating for 30 min, adding 0.5 g of hexadecyltrimethylammonium bromide, stirring for 30 min, adding 5 g of 1,4-bis(triethoxysilyl)benzene, 20 g of phenyltrimethoxysilane and 2 g of vinyltrimethoxysilane, heating to 45° C., stirring for 12 h, centrifuging, washing with water, and washing with alcohol to obtain alkenyl organosilicon-coated boron nitride nanosheets;
[0064] (2) Add 100 g of asphalt to 25 g of cyclohexane oil, heat to 190 °C, stir for 30 min, add 8 g of SBS, continue stirring for 2 h, add 5 g of olefinic organosilicon-coated boron nitride nanosheets and 0.08 g of cumene hydroperoxide, continue stirring for 1 h, add 8 g of talc, continue stirring for 2 h, discharge, and obtain modified asphalt;
[0065] (3) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0066] Comparative Example 5:
[0067] The difference between Comparative Example 5 and Example 2 is that the boron nitride nanosheets wrapped with porous alkenyl organosilicon in step (3) are replaced with boron nitride nanosheets;
[0068] The specific steps are as follows:
[0069] (1) 100 g of asphalt was added to 25 g of cyclohexane oil, the temperature was raised to 190°C, and the mixture was stirred for 30 min. Then 8 g of SBS was added, and the mixture was stirred for 2 h. Then 5 g of boron nitride nanosheets and 0.08 g of cumene hydroperoxide were added, and the mixture was stirred for 1 h. Then 8 g of talc was added, and the mixture was stirred for 2 h. The modified asphalt was obtained.
[0070] (2) The modified asphalt is coated on the surface of the polyester base with a thickness of 4 mm, flattened, and naturally cooled to obtain an asphalt waterproofing membrane.
[0071] Performance Test:
[0072] Basic performance tests: needle penetration of asphalt prepared according to the test examples and comparative examples according to standard GB / T4509-2010, softening point of asphalt prepared according to the test examples and comparative examples according to standard GB / T4507-2014, ductility of asphalt prepared according to the test examples and comparative examples according to GB / T4508-2010.
[0073] Tensile performance test: The tensile properties of the asphalt waterproof membranes prepared in the examples and comparative examples were tested according to standard GB / T328.8.
[0074] Water-impermeability test: The water-impermeability of the asphalt waterproof membranes prepared in the examples and comparative examples was tested according to method B in standard GB / T328.10-2007.
[0075] Heat resistance test: The heat resistance of the asphalt waterproof membranes prepared in the examples and comparative examples was tested according to method A in standard GB / T328.11-2007.
[0076] Table 1 Performance test results
[0077]
[0078] Note: “√” indicates qualified, “×” indicates unqualified.
[0079] Data Analysis:
[0080] It can be seen from the data of Examples 1-3 in Table 1 that the modified asphalt prepared by the present invention has moderate needle penetration, high softening point and large ductility, which indicates that the modified asphalt has good high temperature stability, low temperature crack resistance and room temperature flexibility. The tensile force of the asphalt waterproofing membrane prepared by the modified asphalt reaches 632N / 50mm, the elongation reaches 39.5%, and it has excellent waterproof performance and high temperature resistance. This indicates that the asphalt waterproofing membrane prepared by the present invention meets the requirements of high strength, high temperature resistance, low temperature crack resistance and excellent waterproofness, and is suitable for long-term use in complex environments.
[0081] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the porous organosilicon wrapped with boron nitride nanosheets constructed with phenyltrimethoxysilane as the main body can effectively improve the needle penetration of the modified asphalt, and further improve the softening point and ductility. This is mainly because the porous organosilicon constructed with phenyltrimethoxysilane as the skeleton can synergistically adsorb small molecular organic matter in the asphalt matrix with SBS, thereby reducing its adverse effects on the asphalt performance, and effectively improves the tensile properties, heat resistance and waterproofness of the asphalt waterproof membrane. This is mainly because the introduction of benzene rings improves the compatibility between boron nitride nanosheets and SBS and the asphalt matrix.
[0082] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that the porous organosilicon-coated boron nitride nanosheets constructed with the participation of 1,4-di(triethoxysilyl)benzene can effectively improve the softening point and ductility of the modified asphalt. This is mainly because 1,4-di(triethoxysilyl)benzene effectively adjusts the pore structure and environment of the organosilicon-coated boron nitride nanosheets, thereby enabling the adsorption of more organic small molecules in the asphalt matrix to form an elastic surface structure, thereby improving the softening point and ductility of the modified asphalt. In addition, 1,4-di(triethoxysilyl)benzene further improves the tensile properties and heat resistance of the asphalt waterproofing membrane. This is mainly because the organosilicon-coated boron nitride nanosheets constructed with the participation of 1,4-di(triethoxysilyl)benzene can form an interlaced structure with SBS and macromolecules in the asphalt matrix.
[0083] From the data of Example 3 and Comparative Example 3 in Table 1, it can be seen that the porous organosilicon-wrapped boron nitride nanosheets constructed with the participation of vinyl trimethoxysilane can effectively improve the softening point and ductility of the modified asphalt and adjust the needle penetration. This is mainly because vinyl trimethoxysilane constructs alkenyl groups on the surface of organosilicon, which can form crosslinks with SBS and construct a network structure. The construction of this network structure also further improves the tensile properties and heat resistance of the asphalt waterproofing membrane.
[0084] It can be seen from the data of Example 2 and Comparative Examples 4-5 in Table 1 that the porous structure of the surface of boron nitride nanosheets and the silicone containing alkenyl groups can effectively improve the basic properties of asphalt, and further improve the tensile properties, heat resistance and waterproof properties of the asphalt waterproof membrane prepared therefrom.
[0085] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. An asphalt waterproofing membrane, characterized in that: It is made by coating modified asphalt on the surface of the tire base, flattening it, and cooling it naturally; The preparation method of the modified asphalt is as follows: (1) adding boron nitride nanosheets to a mixed solution of anhydrous ethanol and deionized water, ultrasonicating for 20-40 minutes, then adding hexadecyltrimethylammonium bromide, stirring for 20-40 minutes, then adding 1,4-bis(triethoxysilyl)benzene, phenyltrimethoxysilane and vinyltrimethoxysilane, heating to 40-50° C., stirring for 10-15 hours, centrifuging, washing with water, washing with alcohol, and drying to obtain alkenyl organosilicon-coated boron nitride nanosheets; (2) adding the alkenyl organosilicon-coated boron nitride nanosheets and the hydrochloric acid aqueous solution into anhydrous ethanol, ultrasonicating for 20-40 minutes, refluxing at 95-105° C. for 20-28 hours, centrifuging, washing with alcohol, and drying to obtain porous alkenyl organosilicon-coated boron nitride nanosheets; (3) Add asphalt to cyclohexane oil, heat to 185-195°C, stir for 20-40 minutes, then add SBS, continue stirring for 1.5-2.5 hours, then add porous olefin-based organosilicon-coated boron nitride nanosheets and isopropylbenzene hydroperoxide, continue stirring for 0.5-1.5 hours, then add talcum powder, continue stirring for 1.5-2.5 hours, discharge, and obtain modified asphalt.
2. The asphalt waterproofing membrane according to claim 1, characterized in that: In the step (1), the average thickness of the boron nitride nanosheets is 200-400 nm, and the average sheet diameter is 3-5 μm.
3. The asphalt waterproofing membrane according to claim 1, characterized in that: In the step (1), the weight ratio of the boron nitride nanosheets, anhydrous ethanol, deionized water, hexadecyltrimethylammonium bromide, 1,4-bis(triethoxysilyl)benzene, phenyltrimethoxysilane and vinyltrimethoxysilane is 10:700-1100:50-150:0.3-0.8:3-7:51-25:1-3.
4. The asphalt waterproofing membrane according to claim 1, characterized in that: In the step (2), the weight ratio of the boron nitride nanosheets wrapped by alkenyl organosilicon, the hydrochloric acid aqueous solution and the anhydrous ethanol is 10:8-12:150-250.
5. The asphalt waterproofing membrane according to claim 1, characterized in that: The concentration of the hydrochloric acid aqueous solution in step (2) is 1.5-2.5 mol / L.
6. The asphalt waterproofing membrane according to claim 1, characterized in that: The asphalt in step (3) is 70# asphalt.
7. The asphalt waterproofing membrane according to claim 1, characterized in that: The SBS in step (3) is linear SBS.
8. The asphalt waterproofing membrane according to claim 1, characterized in that: The cyclopentane oil in step (3) is one of cyclopentane oil 4006 and cyclopentane oil 4010.
9. The asphalt waterproofing membrane according to claim 1, characterized in that: In the step (3), the weight ratio of asphalt, cyclohexane oil, SBS, porous olefin-based organosilicon-wrapped boron nitride nanosheets, cumene hydroperoxide and talc is 100:20-30:7-9:3-7:0.06-0.1:6-10.
10. A method for preparing the asphalt waterproofing membrane according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: coating the modified asphalt on the surface of the polyester base with a thickness of 3-5 mm, flattening, and naturally cooling to obtain the asphalt waterproofing coiled material.
Citation Information
Patent Citations
Two-component asphalt anti-stripping agent and preparation method thereof
CN111892823A
High-thermal-conductivity modified asphalt mixture based on carbon fibers and preparation method thereof
CN112552699A
Modified asphalt waterproof coiled material and preparation method thereof
CN117818104A
Drug-loaded nano motor and preparation method and application thereof
CN118121567A
Flame-retardant asphalt-based waterproof coiled material
CN118496779A
Cited By
Anti-aging heat-resistant modified asphalt for road paving
CN120005417A